Strain Dependency of Poisson's Ratio of SLS Printed Auxetic Lattices Subjected to Quasi‐Static and Dynamic Compressive Loading. Issue 8 (3rd June 2019) - Fíla, Tomáš; Koudelka, Petr; Zlámal, Petr; Falta, Jan; Adorna, Marcel; Neuhäuserová, Michaela; Luksch, Jutta; Jiroušek, Ondřej
Abstract : This paper deals with experimental investigation into a strain‐rate dependent function of Poisson's ratio of three auxetic structures subjected to compressive loading. The missing rib, the 2D re‐entrant honeycomb, and the 3D re‐entrant honeycomb lattices printed using selective laser sintering from powdered SS316L austenitic steel are investigated. The samples are subjected to uni‐axial compression under quasi‐static conditions and dynamic conditions using the Split Hopkinson Pressure Bar (SHPB). The deforming specimens are optically observed in order to apply a digital image correlation for evaluation of the in‐plane displacement and strain fields. From the calculated strain fields, the function of Poisson's ratio is calculated for each experiment using different methods taking specific regions of interest of the specimen microstructures into account. The obtained functions of Poisson's ratio are plotted for each microstructure and strain‐rate. The analysis of the results shows that the strain‐rate has a significant influence on the deformation characteristics of all the investigated microstructures yielding differences in the magnitude of the minima of Poisson's ratio and the differences in the maximum overall compressive strain, where the lattices are still auxetic. Abstract : Function of Poisson's ratio of three auxetic structures is experimentally investigated. The specimens are 3D printed from austenitic steel using selective laser sintering. The mechanical properties are evaluated from uni‐axial quasi‐static compression and using Split Hopkinson Pressure Bar experiments (SHPB). The results show that the strain‐rate has a significant influence on the function of Poisson's ratio and magnitude of its minima.